PENGARUH GINI RASIO DAN PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN SERTA KESEHATAN TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) DI INDONESIA TAHUN 2015-2024 - Althira, Avanda Vini; Haq, Naila Laila Rahma; Putri, Shafrida Choiria; Hartanto, Arif Dwi (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2025)
HDI as an important indicator to measure the development of a region. This study aims to analyze the effect of Gini Ratio and government spending in the education and health sectors on the Human Development Index (HDI) in Indonesia in the period 2015-2024. Secondary data that is time series is processed using multiple linear regression analysis. The results of the study indicate that the Gini Ratio and government spending in the education and health sectors simultaneously have a significant effect on the HDI in Indonesia. Government spending in the education sector has a positive and significant effect on the HDI. However, the Gini Ratio and government spending in the health sector did not show a significant effect on the HDI during the study period.